Mission investing in Europe - a meta-analysis - Tizian Fritz; Georg von Schnurbein (University of Basel, Center for Philanthropy Studies (CEPS), 2015)
Mission Investing (MI) is an umbrella term for the practice of non-profit organizations (NPO) to include their mission into their investment policy. Despite the growing popularity of this concept it still greatly lacks a scientific foundation. This article identifies key characteristics of MI by conducting a conceptual discussion. These characteristics include the incorporation of non-monetary goals into the investments process which are closely related to the organization's mission and values as well as the aim of achieving a more effective mission accomplishment through the unification of investment- and grantmaking policy. Further, in the framework of a meta-analysis, this article compares recently published data from across Europe with regard to the current state-of-art of MI. Among the three basic instruments of MI (screening, shareholder advocacy, and proactive mission investing), screening is used the most. – – Unter dem Oberbegriff "Mission Investing" (MI) versteht sich die Praxis bei Nonprofit Organisationen (NPO), das organisationseigene Sachziel in die Anlagestrategie mit einzuschliessen. Trotz stets steigender Popularität fehlt dem Konzept bisher weitgehend eine wissenschaftliche Fundierung. Mittels einer begrifflichen Diskussion identifiziert dieser Beitrag Schlüsselmerkmale des Anlagekonzepts. Diese Merkmale umfassen unter anderem den Einschluss von non-monetären Anlagezielen, welche eng mit dem Organisationszweck verwandt sind, sowie die Zielsetzung der effektiveren Umsetzung des Organisationszwecks durch die Verknüpfung von Anlage- und Förderpolitik. Weiter vergleicht dieser Beitrag im Rahmen einer Metaanalyse neu erschienene Daten zum aktuellen Umsetzungsstand von MI in Europa. Ausgehend von den drei Instrumenten des MI (Screening, Shareholder Advocacy und Proactive Mission Investing) wird dieses derzeit am häufigsten mittels Screening umgesetzt.
Keywords: A13; D64; G11; L31; 330; Charitable Foundations; Investment Policy; Meta-Analysis; Mission Investing; Non-profit Organizations; Value-based Investing; Anlageverhalten; Gemeinnützige Stiftungen; Metaanalyse; Nonprofit Organisationen; zweckgerichtete Investments